Sprinkling irrigation mechanism for garden maintenance - YANG MENGLAN; DAI KANGKANG; WEI HUIYE (2024)
The utility model relates to the field of sprinkling irrigation mechanisms, in particular to a sprinkling irrigation mechanism for garden maintenance, which comprises a storage cylinder, an extension pipe is slidably connected in the storage cylinder, a first motor is fixedly embedded in the lower end of the extension pipe, and a first gear is fixedly mounted at the output end of the first motor. A rack is fixedly embedded in the inner surface of the storage barrel, a mounting plate is fixedly mounted at the upper end of the interior of the extension pipe, and water distribution pipes are symmetrically and fixedly embedded in the mounting plate. According to the utility model, the sprinkling irrigation device can be mounted in a lawn in a garden and can be stored in a soil layer, so that the contact with the outside is reduced, the sprinkling irrigation device is prevented from being rusted under long-time water vapor erosion, the service life of the sprinkling irrigation device is prolonged, and when a perso